PENINGKATAN KETERAMPILAN PROSES SISWA KELAS VII SMP NEGERI 202 JAKARTA MELALUI PENERAPAN PROBLEM BASED LEARNING DENGAN METODE EKSPERIMEN PADA MATERI KALOR - EVY ALDIYAH (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
Departing from the problem of learning the Heat material where there are still students having difficulty understanding it and the lack of student learning activities, then through this classroom action research the author tries to find a solution by changing the learning method. It is expected that there will be an increase in student activity during the learning process of the material and student learning outcomes will increase. The application of the Problem Best Learning learning model with the experimental method is considered appropriate in the process of learning the Heat material in Basic Competencies 3.4. Heat and Its Displacement. The purpose of this classroom action research is to describe an increase in the process skills of class VII students of SMP Negeri 202 Jakarta through the application of the Problem Based Learning learning model with the experimental method on the heat material. The sample of this study were students of class VII-A, learning was carried out during a limited face-to-face learning period in 2 cycles. The application of the Problem Based Learning learning model with the experimental method on heat material can improve the process skills of class VII-A students, as can be seen from the percentage of the final results of group performance. Of the 8 groups of students, only 2 groups with a percentage of performance results of 75% in the good category, the rest there are 6 groups in the very good category with a percentage of 95%. In addition, the application of the Problem Based Learning learning model with the experimental method on heat material can also increase the learning activities of class VII-A students, it can be seen from the significant increase in the percentage of learning activities from 62.50% in the first cycle to 93.06% in the first cycle. II with very good category. In addition to improving students' process skills and student learning activities, the application of the Problem Based Learning learning model with the experimental method on the Heat material also makes students feel happy about learning science, thereby increasing student learning motivation. ABSTRAKBerangkat dari permasalahan pembelajaran materi Kalor dimana masih ada siswa mengalami kesulitan untuk memahaminya serta kurangnya aktivitas belajar siswa, maka melalui penelitian tindakan kelas ini penulis mencoba mencari solusi dengan melakukan perubahan metode pembelajaran. Diharapkan terjadi peningkatan terhadap keaktifan siswa selama proses pembelajaran materi tersebut dan hasil belajar siswapun meningkat. Penerapan model pembelajaran Problem Best Learning dengan metode eksperimen dianggap sesuai dalam proses pembelajaran materi Kalor pada Kompetensi Dasar 3.4. Kalor dan Perpindahannya. Tujuan penelitian tindakan kelas ini adalah mendeskripsikan adanya peningkatan keterampilan proses siswa kelas VII SMP Negeri 202 Jakarta melalui penerapan model pembelajaran Problem Based Learning dengan metode eksperimen pada materi Kalor. Sampel penelitian ini adalah siswa kelas VII-A, pembelajaran dilakukan pada masa pembelajaran tatap muka terbatas dalam 2 siklus. Penerapan model pembelajaran Problem Based Learning dengan metode eksperimen pada materi Kalor dapat meningkatkan keterampilan proses siswa kelas VII-A, terlihat dari persentase hasil akhir kinerja kelompok. Dari 8 kelompok siswa, hanya 2 kelompok dengan persentase hasil kinerja 75% dalam katagori baik, selebihnya ada 6 kelompok dalam katagori sangat baik dengan persentase 95%. Selain itu, penerapan model pembelajaran Problem Based Learning dengan metode eksperimen pada materi Kalor juga dapat meningkatkan aktivitas belajar siswa kelas VII-A, terlihat dari peningkatan persentase aktivitas belajar yang cukup signifikan dari 62,50% pada siklus I menjadi 93,06% pada siklus II dengan katagori sangat baik. Selain meningkatkan keterampilan proses siswa dan aktivitas belajar siswa, penerapan model pembelajaran Problem Based Learning dengan metode eksperimen pada materi Kalor ini juga membuat siswa merasa senang belajar IPA sehingga meningkatkan motivasi belajar siswa.